Finite Element Evaluation of Elasto-Plastic Residual Stresses around Coldworked Fastener Holes - Ab. Rashdi, Abdalla A. (2000)
The present work on the simulation of cold-working process using finite element analysis was devoted to two parts. The first part concerns with axisymmetric finite element analysis of elastic-plastic 2024-T351 aluminium alloy. The material was considered isotropic and a Von Mises yield stress criterion with hardening rule was assumed. The commercial finite element software, LUSAS-13.1, was used to simulate the cold-working process in a 6 mm thick plate with a 6.35 mm diameter hole with 4% radial expansion for three different models. The second part deals with the effect of support position along the exit face on the residual stress distribution around the hole. Finite element analysis of eight axisymmetric models with different support positions was considered. The finite element results for first part of the analysis showed that the radial residual stresses were of a compressive nature, except for a thin layer on the entrance face of the specimen. Models 1 and 2 gave a lesser spread of compressive tangential residual stresses data than that obtained from model 3. The tangential residual stresses at the entrance face were tensile in nature while beyond 1 mm from the top surface through the rest of the thickness and along the edge of the hole they were compressive in nature. The results were compared with previous results in the literature and good agreement was obtained. The analysis of the second part showed that the distribution of the tangential residual stresses at the exit face suggest the superiority of the support conditions 7 and 8 compared to support conditions 1 to 6. The magnitude of the spurt in value of the residual stresses varied with support condition and finally reduced to zero for support condition starting from 15 to 20 mm from the edge of the hole.